MANUFACTURING PROCESS OPTIMIZATION VIA JIGS DEVELOPMENT: IMPROVING SAFETY AND EFFICIENCY IN LOCOMOTIVE ASSEMBLY - Sovetkazin, Alisher; Adilbek, Bekzat; Bespalinova, Kamilla; Khobdabayev, Nursat (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This capstone project addresses inefficiencies and safety concerns in the industry of locomotive assembly by developing custom jigs and fixtures. Current methods of aligning components are inefficient and mostly have been performed by cranes, resulting in time delays and safety hazards. In this frame, this project is dedicated to designing and integrating jigs that optimize alignment precision, workflow efficiency, and operator safety. The methodology includes conventional workflow analysis, application of ergonomic principles, and advanced manufacturing techniques in designing along with developing jig and fixture prototypes. It is argued that designed products are expected to minimize manual effort and reduce reliance on cranes, leading to improved assembly and prevented risks of downtime. Beyond improving assembly efficiency, it redefines traditional manufacturing concepts through integrating new design and applying engineering principles. These findings contribute to not only advancements in locomotive manufacturing but also can be applicable for other industries that may require efficient and safe assembly of large components.
Keywords: type of access: open access